PLUMBUM (Pb) CONCENTRATION IN ANNUAL BANDS OF CORAL Porites lutea AT TUNDA ISLAND, BANTEN - . Riska; Neviaty P. Zamani; Tri Prartono; Ali Arman (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Coral is one of marine organisms that can accumulate heavy metals such as Pb in its skeleton. The purpose of this study was to determine the concentration of heavy metals Pb in growth bands of coral P. lutea at windward and leeward regions of Tunda Island. The results showed that P. lutea accumulated heavy metals Pb in their growth bands. The results of Pb concentrations in windward region were in range of 6.17-14.76 mg kg-1/year, with the average concentration rate of 9.69 mg kg-1/year.  Meanwhile, in leeward region, the Pb concentrations were in range of 8.37-17.66 mg kg-1/year whith the average concentration rate of 13.33 mg kg-1/year. The Pb concentration in leeward regions was higher than in the windward region. Keywords: heavy metal Pb, coral P. lutea, Tunda Island